Analysis of Parental Support and Role in Elementary School Age Literacy Learning - Annisa, Fatimah Azzikri; Nisa, Sahrun; Suriani, Ari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the support and role of parents in the literacy learning of elementary school children. The study examines various forms of parental support, including the provision of a conducive reading environment, active involvement in literacy activities, and collaboration with teachers. Through a systematic literature review method analyzing several articles, it was found that parental support significantly contributes to the development of children's literacy skills. Parents who are actively involved in their children's literacy learning can enhance their reading interest, reading skills, and self-confidence. The findings of this study highlight the importance of parental roles in supporting literacy education at home and suggest strategies that can be implemented to increase parental involvement in their children's learning process.